1999
DOI: 10.1177/00139169921972272
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Norms and Assumed Consequences on Recycling Behavior

Abstract: Given the aim to motivate consumers to behave in an environmentally friendly manner, there is a need to understand how consumers’ environmental behavior can be influenced and what variables predict environmental behavior. This article applies structural equation models (path analyses) to investigate these issues, with experienced social norm, assumed consequences of behavior and personal norm as independent variables of recycling behavior. The study is based on a Norwegian survey. As predicted, the social norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
139
0
18

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(171 citation statements)
references
References 38 publications
(41 reference statements)
14
139
0
18
Order By: Relevance
“…Some authors report a correlation between moral norms and recycling behaviour [4, 7, 9, 22, 24, 26, 30-32, 37, 39, 44, 47, 48, 53, 59, 67, 71-78]. Only five studies included in our meta-analysis found no significant relationship between moral norms and behaviour [8,27,28,36,62].…”
Section: Socio-psychological Group Of Variablesmentioning
confidence: 74%
See 3 more Smart Citations
“…Some authors report a correlation between moral norms and recycling behaviour [4, 7, 9, 22, 24, 26, 30-32, 37, 39, 44, 47, 48, 53, 59, 67, 71-78]. Only five studies included in our meta-analysis found no significant relationship between moral norms and behaviour [8,27,28,36,62].…”
Section: Socio-psychological Group Of Variablesmentioning
confidence: 74%
“…All sources analysed (Fig. 6) report that access to kerbside recycling stimulates recycling behaviour and increases recycling of all material types [4,9,22,26,49,54,61,62]. According to the authors, this indicates that recycling based on any system other than kerbside (property closed) collection (mostly drop-off stations involving storage, time and transport costs for individuals) can lower participation.…”
Section: Technical-organisational Group Of Variablesmentioning
confidence: 97%
See 2 more Smart Citations
“…Stern et al 1999) as well as specific environment-related behaviours. Specific environmental behaviour studies include yard burning behaviour (van Liere and Dunlap 1978); reducing car use (Eriksson et al 2006;Nordlund and Garvill 2003); reducing emissions from diesel cars (Steg and de Groot 2010); recycling (Bratt 1999;Hopper and Nielsen 1991); and general pro-environmental behaviour (Schultz et al 2005, Nordlund andGarvill 2002). It has also been applied in relation to WTP for environmental goods , Liebe et al 2011, Guagnano et al 1994, Guagnano, 2001, Blamey 1998, but only in the context of contingent valuation.…”
Section: The Norm Activation Model (Nam)mentioning
confidence: 99%